Formation of Ti-Al-N dispersed layer on steel surface by TIG melting in a reactive environment - Dyuti, Sarker; Mridha, Shahjahan; Shaha, Sugrib Kumar (Trans Tech Publications Inc., 2011)
In this study an attempt has been made to produce titanium-aluminium dispersed hard nitride layer on mild steel surfaces by preplacement of 50 % Ti and 50 % Al powder mixture and then melting with TIG torch under nitrogen environment. Parameter such as heat input of the torch was varied between 540, 608 and 675 J/mm and its effect on the resolidified melt pool was studied. Glazing under all energy inputs produced more than 1mm thick resolidified clad layer. The microstructural analysis revealed the clad layer with dispersion of dendrites of Ti-Al nitrides and Ti-Al intermetallic in ferrite matrix. The concentration of dendrites were found to be maximum near the surface and decreased at deeper depths.The maximum hardness of the modified surface layer was found to be 900 Hv compared to 180 Hv of the mild steel substrate.